2021
DOI: 10.1177/2325967121994548
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Trochlear Osseous Morphology: An Epidemiologic Study

Abstract: Background: The femoral trochlea is considered the most significant osseous factor affecting stability in the patellofemoral joint. The true prevalence of trochlear dysplasia in the general population is largely unknown. Purpose/Hypothesis: To investigate the prevalence of trochlear dysplasia in the general population. Our hypothesis was that, while trochlear dysplasia is not uncommon, there is a low prevalence of severe dysplasia in the general population. Study Design: Descriptive epidemiology study. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Of the remaining 1,810, a further 1,743 were irrelevant based on their title and/or abstract. Full‐text screening of the remaining 67 eligible studies resulted in exclusion of 37 irrelevant studies [1–3, 5, 6, 8–11, 13, 14, 21, 23–25, 28, 29, 32, 33, 37, 38, 42, 44–46, 51, 55–57, 60, 61, 63, 66–70], five studies that did not report intra‐ or inter‐observer agreement [2, 35, 43, 52, 61], four studies that were conference proceedings [40, 49, 53, 59], two studies that assessed agreement for classification systems other than Dejour classification [34, 48], one study that included skeletally immature patients [15], two studies that expressed inter‐observer agreement only as a percentage [36, 64], three studies that were not in English or French [12, 39, 71] and three studies that could not be retrieved [7, 19, 47]. No additional studies were identified from reference lists, which left ten relevant studies for data extraction [4, 6, 22, 30, 31, 39, 41, 54, 58, 65].…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 1,810, a further 1,743 were irrelevant based on their title and/or abstract. Full‐text screening of the remaining 67 eligible studies resulted in exclusion of 37 irrelevant studies [1–3, 5, 6, 8–11, 13, 14, 21, 23–25, 28, 29, 32, 33, 37, 38, 42, 44–46, 51, 55–57, 60, 61, 63, 66–70], five studies that did not report intra‐ or inter‐observer agreement [2, 35, 43, 52, 61], four studies that were conference proceedings [40, 49, 53, 59], two studies that assessed agreement for classification systems other than Dejour classification [34, 48], one study that included skeletally immature patients [15], two studies that expressed inter‐observer agreement only as a percentage [36, 64], three studies that were not in English or French [12, 39, 71] and three studies that could not be retrieved [7, 19, 47]. No additional studies were identified from reference lists, which left ten relevant studies for data extraction [4, 6, 22, 30, 31, 39, 41, 54, 58, 65].…”
Section: Resultsmentioning
confidence: 99%
“…Trochlear dysplasia has been recognized as the most common factor in patients with patellofemoral dislocation [38]. Trochleoplasty is a surgical procedure whose primary goal is to modify the femoral trochlea’s abnormal shape in patients suffering from patellar instability.…”
Section: Discussionmentioning
confidence: 99%
“…Values below 3 mm are in favor of TD. These values are important parameters for patellofemoral instability associated with TD [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%